Examining the Impact of Corporate Dividend Policy On Stock Price Volatility In Singapore : Does Financial Crisis Matter? - Hussain, Muhammad Asjad (2016)
One of the most puzzling and widely researched topics in the field of corporate finance is corporate dividend policy and the probable impact it has on firms’ stock price volatility. Despite years of research and extensive empirical examination of the dividend policy-stock price volatility linkage, conflicting evidence across a multitude of studies implies that no solid conclusion regarding the veracity and validity of this relationship has yet been reached. Furthermore, there is a dearth of studies that seek to examine how periods of economic and financial uncertainty, brought about by a financial crisis, affect the underlying relationship. Also owing to the lack of studies undertaken in the Southeast Asian context, this paper seeks to investigate the dividend policy-price volatility linkage with and without the context of a financial crisis in Singapore, with panel data obtained from 30 non-financial Singaporean firms over the sample period of 2004 to 2014. In line with Baskin’s (1989) seminal study, dividend yield and dividend payout ratio are used as proxies for dividend policy and as the main independent variables; stock price volatility serves as the main dependent variable. In order to add robustness and obtain realistic results, we control for other firm-specific factors that could affect both dividend policy and stock prices: Earnings per share, firm size, earnings volatility, leverage, and asset growth are added as control variables along with a crisis dummy variable that characterizes the impact of the recent 2007-08 Global Financial Crisis. Pooled ordinary least squares (OLS) regression and cross-section Fixed and Random Effects are applied to carry out the analysis but according to the Hausman test, only the Random Effects model turns out to be more appropriate and efficient for our panel study. The results from the cross-section Random Effects model indicate that stock price volatility is significantly and negatively associated with both dividend payout ratio and firm size with strong support for the dividend signaling hypothesis in Singapore. Our study also records evidence corroborating Baskin’s (1989) rate of return theory that Singapore firms with high dividend payout exhibit lower volatility in their share prices. Although the crisis dummy variable positively contributes to share price volatility, this relationship is statistically insignificant and thus highlights the resilience of Singapore firms to maintain dividend payments as well as stabilize share prices even during a financial crisis contagion.